SI PAISUCEN: MODIFICATION OF PHARMACEUTICAL INVENTORY SYSTEM Dr. SAIFUL ANWAR GENERAL HOSPITAL - Puspitasari, Vicky; Widhayunita, Lya (Universitas Brawijaya, 2025)
The implementation of the pharmaceutical inventory system at Dr Saiful Anwar Hospital (RSSA), SI PAISUCEN or Sistem Informasi Pharmaceutical Supply Chain with an integrated Pharmaceutical Supply Chain Management (PSCM) approach, still encounters several problems. For this reason, RSSA management modified the inventory system. This research aims to describe the development of the system and find out the results. This study uses a quantitative descriptive approach conducted on the pharmacy inventory system of Dr. Saiful Anwar Hospital. Secondary data in the form of the annual report of Pharmacy Department in 2021-2022 is used to evaluate the effectiveness of the implementation of SI PAISUCEN. The development of SI PAISUCEN features for the 2021-2022 period is carried out in six categories of activities including planning, procurement, receipt, use, reporting, and evaluation. The development of the SI PAISUCEN feature showed positive results in the form of a reduction in costs due to near-expiration by 82.7% for drugs and 69.1% for medical devices, faster information presentation, more accurate data, and better control of stock of goods. The success of the development of SI PAISUCEN can increase the effectiveness and efficiency of pharmaceutical management in hospitals in general.